Semi-síntese de novos derivados da caulerpina e avaliação da atividade leishmanicida do ácido caulerpínico - Sousa, Jéssica Celestino Ferreira (2016)
The Caulerpa genus was recognized by Lamouroux as the Caulerpaceae family, belonging to the order of Bryopsidales. Species and subspecies of this genus are distributed mainly in tropical and subtropical seas. The major substance of this genus is the caulerpina, bis-indolealkaloid, firstisolated in 1970 from the species Caulerpa racemosa. Several studies using caulerpina showed various biological activities such as antioxidant, antifungal, acetylcholinesterase inhibitor, antinociceptive and anti-inflammatory, as well as antiviral and anti tumor effect. According to the pharmacological potential of this molecule, further studies were performed to develop analogues by introducing new substituents can result in significant chemical differences and different pharmacokinetic properties. This study aims to isolate caulerpine; make structural modifications to obtain novel analogues of caulerpine; and assess the potential cytotoxic and leishmanicide of caulerpine and derivatives. From the ethanol extracto the Caulerpa racemosa was possible to isolate the caulerpines ubstance and from performed semi-synthesis was obtained the following derivatives, (6E, 13E)-5,12-dihydrocycloocta [1,2-b: 5, 6-B']diindole-6,13-dicarboxylic acid, as described in the literature and other novel derivatives in the literature: (6E, 13E)-dibutyl 5, 12 dihydrocycloocta[1,2-b: 5,6-b'] diindole-6,13-dicarboxylate; (6E, 13E)-diisobutyl 5, 12dihydrocycloocta[1,2-b: 5,6- b']diindole-6,13-dicarboxylate;(6E, 13E)-dipropyl 5, 12 dihydrocycloocta[1,2-b: 5,6- b']diindole-6,13-dicarboxylate; (6E, 13E)-diethyl 5, 12 dihydrocycloocta[1,2-b: 5,6- b']diindole-6,13-dicarboxylate; (6E, 13E)-dipentyl5, 12 dihydrocycloocta[1,2-b: 5,6- b']diindole-6,13-dicarboxylate; (6E, 13E)-diisopentyl 5, 12 dihydrocycloocta[1,2-b: 5,6-b']diindole-6,13-dicarboxylate; (6E, 13E)-diallyl 5, 12 dihydrocycloocta[1,2-b: 5,6-b']diindole-6,13-dicarboxylate; (6E,13E)-dimethyl5,12-diacetyl 5, 12 dihydrocycloocta[1,2-b: 5,6-b']diindole-6,13-dicarboxylate. All chemical constituents were identified by infrared spectroscopic techniques and 1H and 13C NMR. The CLP and caulerpinic acid study demonstrated significant activities against promastigtes of Amazon Leishimania.